2002
DOI: 10.1115/1.1454113
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Comparative Study of Compressor Rotor and Stator Blade Deposition Rates

Abstract: Compressor fouling is generally accepted to be an important factor when monitoring the efficiency of an engine’s operation. However, there are not many studies related to the local fouling behavior of the individual components of the compressor. In the present paper, the CFD-ACE software package is used for the flow field calculation and the results are utilized to calculate the deposition rates on the blade surfaces of a conventional compressor stator and rotor. The deposition model takes into account the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Traditional flow simulation anlaysis method for fouled compressor [8][9] [10] Because fouling of compressor blade increases surface roughness, many researchers simulate the fouling phenomenon by specifying a constant roughness for blade. Another method used by researchers is that a surface is adhered to blade to construct the model of fouled compressor.…”
Section: Flow Simulation Of Compressormentioning
confidence: 99%
“…Traditional flow simulation anlaysis method for fouled compressor [8][9] [10] Because fouling of compressor blade increases surface roughness, many researchers simulate the fouling phenomenon by specifying a constant roughness for blade. Another method used by researchers is that a surface is adhered to blade to construct the model of fouled compressor.…”
Section: Flow Simulation Of Compressormentioning
confidence: 99%
“…The results show that increasing turbulence intensity is helpful to reduce pressure drop and enhance heat transfer efficiency of recuperator [5] . Bouris et al has carried on the numerical calculation to the heat transfer mechanism of the heat transfer tube in the recuperator, and has drawn the conclusion that the use of the oval-tube increases the heat transfer rate, because the lower pressure drop caused by the shape of the tube makes the tube can be placed on the closer spacing [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The research indicated that fouling may cause a drop in airflow, pressure ratio, compressor efficiency, and compressor performance, resulting in a “rematching” between the gas turbine and compressor, and a subsequent drop in power output and thermal efficiency . The fouling phenomenon in the compressor was caused by many factors, such as the number of particles, particle diameters, particle mass concentration, patterns of particle distribution, and particle mass flow rate . Meanwhile, the design parameters of the axial compressor also influenced the process of fouling formation, such as axial compressor chord length, solidity, roughness, and the number of stages .…”
Section: Introductionmentioning
confidence: 99%
“…22 The fouling phenomenon in the compressor was caused by many factors, such as the number of particles, particle diameters, particle mass concentration, patterns of particle distribution, and particle mass flow rate. 4,[30][31][32][33][34][35][36][37] Meanwhile, the design parameters of the axial compressor also influenced the process of fouling formation, such as axial compressor chord length, solidity, roughness, and the number of stages. 22,[30][31][32][33][36][37][38] In addition, studies of the transport process of solid particles in an axial compressor 31,32,36,37 and the kinematic characteristics of particle deposition 34,39,40 were helpful in researching the mechanism of solid particle deposition.…”
Section: Introductionmentioning
confidence: 99%